2000
DOI: 10.1093/jac/46.6.981
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid against penicillin-sensitive and -resistant pneumococci in the rabbit meningitis model

Abstract: Linezolid, a new oxazolidinone antibiotic, showed good penetration (38+/-4%) into the meninges of rabbits with levels in the CSF ranging from 9.5 to 1.8 mg/L after two i.v. injections (20 mg/kg). Linezolid was clearly less effective than ceftriaxone against a penicillin-sensitive pneumococcal strain. Against a penicillin-resistant strain, linezolid had slightly inferior killing rates compared with the standard regimen (ceftriaxone combined with vancomycin). In vitro, linezolid was marginally bactericidal at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 11 publications
1
30
0
1
Order By: Relevance
“…In a study with a rabbit meningitis model, the authors noted that linezolid showed good penetration into the cerebrospinal fluid of rabbits (mean Ϯ SD, 38% Ϯ 4%) (8). In a limited study of CSF penetration in patients with ventricular-peritoneal shunts and noninflamed meninges, the CSF concentration/plasma concentration ratio was 0.7:1.0 after multiple linezolid doses (18).…”
Section: Discussionmentioning
confidence: 99%
“…In a study with a rabbit meningitis model, the authors noted that linezolid showed good penetration into the cerebrospinal fluid of rabbits (mean Ϯ SD, 38% Ϯ 4%) (8). In a limited study of CSF penetration in patients with ventricular-peritoneal shunts and noninflamed meninges, the CSF concentration/plasma concentration ratio was 0.7:1.0 after multiple linezolid doses (18).…”
Section: Discussionmentioning
confidence: 99%
“…The use of this model greatly helped the understanding of several aspects of pneumococcal meningitis, including bacterial replication in the CSF, host defenses and inflammation, BBB alteration, and also the systemic effects of meningitis on animal respiration and circulation (236). Numerous studies have been undertaken to evaluate antibiotic efficacy (34,64,73,85,172,189,203,226,231) and the role of host and bacterial factors in disease pathogenesis (10,36,247). Interestingly, the effectiveness of a bactericidal but nonbacteriolytic antibiotic, such as daptomycin, in clearing pneumococcal infection from the CSF and in reducing inflammation was proven by means of both this rabbit model (226) and a previously described rat model (94).…”
Section: Rat and Rabbit Modelsmentioning
confidence: 99%
“…A recent study using the rabbit meningitis model studied the efficacy of linezolid against penicillin-sensitive and penicillin-resistant pneumococci (41). The authors noted that linezolid showed good penetration into the cerebrospinal fluid of rabbits (mean [ϮSD], 38% Ϯ 4%).…”
Section: Reviewmentioning
confidence: 99%